2003
DOI: 10.1016/s0378-1097(03)00376-8
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of the mosaic structure of the four internal transcribed spacers and localisation of the rrn operons on the Streptococcus pneumoniae genome

Abstract: The detection of heterogeneity of the 16S^23S ribosomal intergenic transcribed spacer (ITS) region has become rather common over the past years for identification and typing purposes of bacteria. The ITS not only varies in sequence and length, but also in number of alleles per genome and in their position on the chromosome together with the ribosomal clusters. The ITS characterisation has allowed discrimination of several species within a genus and variation in ITS sequences between the multiple rrn operons pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…This has been possible due to the high interand intraspecific variability (8,17,33,34,40). The advantage of this region is that the flanking 16S and 23S rRNA genes at the 5Ј and 3Ј ends of the ISR contain highly conserved sequences (i.e., the 16S and 23S rRNA genes).…”
Section: Discussionmentioning
confidence: 99%
“…This has been possible due to the high interand intraspecific variability (8,17,33,34,40). The advantage of this region is that the flanking 16S and 23S rRNA genes at the 5Ј and 3Ј ends of the ISR contain highly conserved sequences (i.e., the 16S and 23S rRNA genes).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that bacterial genomes can contain several rrn operons, e.g. Enterococcus has three copies of this operon [27] and Streptococcus pneumoniae has four operons [28]. The ITS sequence tends to present a mosaic organization of blocks, highly conserved at intra-and interspecies level, within the genus Streptococcus [28].…”
Section: Discussionmentioning
confidence: 99%
“…Enterococcus has three copies of this operon [27] and Streptococcus pneumoniae has four operons [28]. The ITS sequence tends to present a mosaic organization of blocks, highly conserved at intra-and interspecies level, within the genus Streptococcus [28]. But in other genera, both length and copy number can vary from strain to strain [26].…”
Section: Discussionmentioning
confidence: 99%
“…In silico analysis of ISR length variability in 27 genomically sequenced bacterial species revealed that while in some species ISR length is variable within and between isolates, in others ISR lengths are limited to one or two sizes, usually dependent on the number of tRNAs present (Christensen et al, 1999). For example, while the multiple copies of the S. enterica serovar Typhimurium, serovar Infantis, and serovar Derby ITS fragments are polymorphic, they are conserved in other Salmonella species, as well in Listeria, Streptococcus, and certain species of Staphylococcus (Giannino et al, 2003;Gurtler & Stanisich, 1996;Lagatolla et al, 1996;Marsou et al, 1999). As consequence depending of the construction of rRNA operon amplification of its noncoding fragments can be a very useful technique for identifying bacteria to the species level (if the sequence is conserved) or for their differentiation if the target fragment of gene characterize with high polymorphism.…”
Section: Fig 1 Organization Of Bacterial Rrna Operonmentioning
confidence: 99%